Implementasi Model Seminar Kontekstual untuk Penguatan Identitas Kristiani Mahasiswa di Institut Teknologi Batam (ITEBA) - Agiana Her Visnhu Ditakristi; Joni Manumpak Parulian Gultom; Vicky BGD Paat; Lucky Sariowan (Institut Kristen Teologi Real Batam, 2026)
This Community Service (PkM) activity aims to strengthen the Christian identity of students at the Batam Institute of Technology (ITEBA) through a contextual seminar model based on an understanding of Christology and Soteriology. The background to this activity is the challenges of the digital era and globalization that influence the formation of Christian student identity, especially in the technology college environment. Therefore, this PkM activity is considered important by the Doctoral Study Program of STT REAL Batam. The goal is for Christian students to maintain a correct understanding of the foundations of Christology and Soteriology. The method used is a participatory contextual seminar with an educational-transformational approach, involving 40 Christian students at ITEBA. The implementation stages include needs analysis, module development, three seminar sessions, and evaluation through pre-tests, post-tests, spiritual motivation questionnaires, and qualitative reflections. The results of the activity showed a significant increase in participants' theological understanding based on a comparison of pre-test and post-test scores. In addition, participant reflections indicated an increased integrative awareness between faith and academic life and a commitment to living out Christian identity in the context of technology and social service. Therefore, this contextual seminar model has proven effective as a strategy for fostering Christian identity in students at technology universities and has the potential to be replicated in similar contexts. This activity recommends that ITEBA integrate contextual faith development into its ongoing student character development program. Keywords: Christian identity; christology; soteriology; contextual seminar; technology college Abstrak Kegiatan Pengabdian kepada Masyarakat (PkM) ini bertujuan untuk memperkuat identitas Kristiani mahasiswa Institut Teknologi Batam (ITEBA) melalui model seminar kontekstual berbasis pemahaman Kristologi dan Soteriologi. Latar belakang kegiatan ini adalah tantangan era digital dan globalisasi yang memengaruhi pembentukan identitas mahasiswa Kristen, khususnya di lingkungan perguruan tinggi teknologi. Oleh karena itu kegiatan PkM ini dipandang penting oleh Program Studi Doktor STT REAL Batam. Tujuannya agar mahasiswa Kristen tetap memahami dasar Kristologi dan Soteriologi dengan benar. Metode yang digunakan adalah seminar kontekstual partisipatif dengan pendekatan edukatif–transformasional, melibatkan 40 mahasiswa Kristen ITEBA. Tahapan pelaksanaan meliputi analisis kebutuhan, penyusunan modul, pelaksanaan tiga sesi seminar, serta evaluasi melalui pre-test, post-test, angket motivasi spiritual, dan refleksi kualitatif. Hasil kegiatan menunjukkan adanya peningkatan pemahaman teologis peserta secara signifikan berdasarkan perbandingan skor pre-test dan post-test. Selain itu, refleksi peserta mengindikasikan meningkatnya kesadaran integratif antara iman dan kehidupan akademik serta komitmen untuk menghidupi identitas Kristen dalam konteks teknologi dan pelayanan sosial. Oleh karenanya model seminar kontekstual ini terbukti efektif sebagai strategi pembinaan identitas Kristiani mahasiswa di perguruan tinggi teknologi dan berpotensi direplikasi dalam konteks serupa. Kegiatan ini merekomendasikan agar ITEBA mengintegrasikan pembinaan iman kontekstual dalam program pengembangan karakter mahasiswa secara berkelanjutan. Kata kunci: identitas Kristiani; kristologi; perguruan tinggi teknologi; seminar kontekstual; soteriologi